2014
DOI: 10.1007/s00330-014-3508-z
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary clinical experience with a dedicated interventional robotic system for CT-guided biopsies of lung lesions: a comparison with the conventional manual technique

Abstract: • CT-guided biopsy is the main procedure to obtain diagnosis in lung tumours. • The robotic device facilitates percutaneous needle placement under CT guidance. • Robot-assisted CT-guided lung biopsy reduces procedure duration and radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…On the other hand, real-time monitoring of lesions movement with CT-fluoroscopy guidance allows reducing needle passes and procedure time; however, the radiation dose (to both the patients and operator) is significant [28]. To simplify the approach and to increase the speed and reliability of step-and-shoot CT-guided chest biopsies, several technical advances have been proposed, including augmented reality and use of robotic platforms [29].
Fig.
…”
Section: Imaging Guidance Techniquesmentioning
confidence: 99%
“…On the other hand, real-time monitoring of lesions movement with CT-fluoroscopy guidance allows reducing needle passes and procedure time; however, the radiation dose (to both the patients and operator) is significant [28]. To simplify the approach and to increase the speed and reliability of step-and-shoot CT-guided chest biopsies, several technical advances have been proposed, including augmented reality and use of robotic platforms [29].
Fig.
…”
Section: Imaging Guidance Techniquesmentioning
confidence: 99%
“…133,134,137 Several advanced transthoracic approaches using optical navigation, electromagnetic navigation, and robotics are under investigation; it is still to be determined whether these systems enhance diagnostic rates and reduce complications relative to experienced interventional radiologists. [141][142][143][144]…”
Section: Optimization Of Tissue Sampling Techniquesmentioning
confidence: 99%
“…A brief literature review of the state of the art on robot‐assisted puncture research is presented in the following. Anzidei et al compared 100 cases of robot‐assisted percutaneous lung biopsy with conventional percutaneous lung biopsy, and the results showed that the robot group had higher accuracy and safety. Zhao et al studied the robot‐assisted puncture system and analyzed the techniques of modeling, planning, navigation, and control.…”
Section: Introductionmentioning
confidence: 99%